The determinants of performance appraisal systems: A note (do Brown and Heywood's results for Australia hold up for Britain?) - John T. Addison; Clive R. Belfield (Institute for the Study of Labor (IZA), 2007)
This paper offers a replication for Britain of Brown and Heywood's analysis of the determinants of performance appraisal in Australia. Although there are some important limiting differences between our two datasets - the AWIRS and the WERS - we reach one central point of agreement and one intriguing shared insight. First, performance appraisal is negatively associated with tenure: where employers cannot rely on the carrot of deferred pay or the stick of dismissal to motivate workers they will tend to rely more on monitoring, ceteris paribus. Alternatively put, when the probability of job separation is greater, the influence of deferred compensation diminishes. Second, there is also some suggestion in the data that employer monitoring and performance pay may be complementary. However, consonant with the disparate results from the wider literature, there is more modest agreement on the contribution of specific HRM practices, and still less on the role of job control. Finally, there is no carry over to Britain of the structural determinants identified by Brown and Heywood.
Keywords: 650; Performance appraisal; monitoring; deferred compensation; performance pay; HRM practices; worker tenure; unionism; Personalbeurteilung; Leistungskontrolle; Leistungsorientierte Vergütung; Betriebszugehörigkeit; Gewerkschaftlicher Organisationsgrad; Großbritannien